Optimization technique for finding conditional expression using nested indexes - Châu, Trương Ngọc; Ban, Đoàn Văn (Journal of Computer Science and Cybernetics, 2012)
In large databases in general and Object-Oriented Database in particular, the queries on databases often contain conditional expression finding including complicated conjunctions and disjunctions. This article studies and proposes ways to optimize complicated finding conditional expression, which have container path expressions using nested indexes.